The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1518-8345.2633.3056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the practice environment of nurses on job outcomes and safety climate

Abstract: Objective:to propose and analyze a theoretical model to measure the effect of nurses’ perceptions about the practice environment on safety climate, job satisfaction, intention to stay employed and in the profession, and burnout syndrome. Method:correlational study with probabilistic sample of 465 nurses. In the theoretical model, the dimensions of the nursing practice environment were considered as independent variables and job satisfaction, safety climate, intention to stay employed and in the profession, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The above findings show the susceptibility to BS development in professionals who works at ICU, particularly nursing technicians, for being at the bedside, and directly exposed to emotionally intense situations such as illness, death and family (1)(2)(3) .…”
Section: Human Services Survey Scores Among Workersmentioning
confidence: 77%
See 1 more Smart Citation
“…The above findings show the susceptibility to BS development in professionals who works at ICU, particularly nursing technicians, for being at the bedside, and directly exposed to emotionally intense situations such as illness, death and family (1)(2)(3) .…”
Section: Human Services Survey Scores Among Workersmentioning
confidence: 77%
“…Intensive Care Units (ICUs) are specialized units that serve severely affected patients daily. Patients' suffering and death, work overload, complexity of actions, lack of human and material resources, performance of high-risk procedures, excessive noise, closed environment and artificial lighting, among others, are factors that generate stress and fatigue in workers of these units (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…Diverse authors have identified greater Rev Gaúcha Enferm. 2020;41:e20190381 professional satisfaction (14,19,22,24,31,54) , higher involvement and commitment in the professionals (35,46,50) , lower levels of burnout (9,14,19,22,54) , lower intent to leave the work (9)(10)19,22,54,56) , and better perception on the quality of care (22,54) . In relation to the patients, greater satisfaction with care and lower mortality rates (22,(38)(39) were verified.…”
Section: Discussionmentioning
confidence: 99%
“…Costa N et al, 2018 (13) Brazil Nursing Work Index -Revised: Brazilian Version Dorigan G and Guirardello E, 2018 (14) Brazil Papastavrou E et al, 2015 (33) Cyprus Revised Professional Practice Environment…”
Section: Instruments For Assessing the Professional Nursing Practice mentioning
confidence: 99%
“…(2) In the 1990s, the American Nurses Credentialing Center (ANCC) developed a voluntary recognition program for formal accreditation of the MHs, and since then, researches have been conducted with the intention of developing and improving instruments to evaluate the presence of characteristics that favor professional practice of nursing, as well as to evaluate the relationship between these characteristics and the results with patients, professionals and institutions. (3)(4)(5)(6)(7)(8) According to the International Council of Nurses, it is critically important to recognize the determinant factors for favorable environments, because they contribute for the promotion of an excellence care, maximizing the health and well-being of the professionals and improving the results for patients and organizational performance. (9) Based on this assumption, among the tools developed for this purpose, the Practice Environment Scale (PES) stands out because, besides having satisfactory measurement properties, (10) this scale allows the classification of the environments in the institutions as miscellaneous, favorable and unfavorable (11) and therefore, can be used to compare scenarios, predict results and guide the evaluation of interventions.…”
Section: Introductionmentioning
confidence: 99%